Stability and Delay of Network-Diversity Multiple Access with Multiple Antenna Reception in Rice Fading Correlated channels using Backlog Retransmission Control - Robles, Ramiro (2019)
This paper investigates backlog retransmission strategies for a class of random access protocols with retransmission diversity (i.e., network diversity multiple access or NDMA) combined with multiple-antenna-based multi-packet reception (MPR). This paper proposes NDMA-MPR as a candidate for 5G contention-based and ultra-low latency multiple access. This proposal is based on the following known features of NDMA-MPR: (1) near collision-free performance, (2) very low latency values, and (3) reduced feedback complexity (binary feedback). These features match the machine-type traffic, real-time, and dense object connectivity requirements in 5G. This work is an extension of previous works using a multiple antenna receiver with correlated Rice channels and co-channel interference modelled as a Rayleigh fading variable. Two backlog retransmission strategies are implemented: persistent and randomized. Boundaries and extended analysis of the system are here obtained for different network and channel conditions. Average delay is evaluated using the M/G/1 queue model with statistically independent vacations. The results suggest that NDMA-MPR can achieve very low values of latency that can guarantee real- or near-real-time performance for multiple access in 5G, even in scenarios with high correlation and moderate co-channel interference.